2020
DOI: 10.18268/bsgm2020v72n1a111219
|View full text |Cite
|
Sign up to set email alerts
|

The use and misuse of magnetic methods to monitor environmental pollution in urban areas

Abstract: Invited article The use and misuse of magnetic methods to monitor environmental pollution in urban areas Uso y abuso de métodos magnéticos en el monitoreo de contaminación ambiental en áreas urbanas

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 3 publications
0
14
0
2
Order By: Relevance
“…Rock magnetism was extensively used also for biomonitoring airborne pollution using tree leaves, barks, mosses and lichens, being efficient PM receptors; for a review, see Hofman et al (2017) , thereinafter, Winkler et al (2019) , Marié at al. (2020) : the magnetic properties of PM filters and bioaccumulators depend on the concentration and the grain-size of magnetite-like minerals accumulated on the samples, with the magnetic susceptibility being the fastest and most used parameter ( Kapper et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Rock magnetism was extensively used also for biomonitoring airborne pollution using tree leaves, barks, mosses and lichens, being efficient PM receptors; for a review, see Hofman et al (2017) , thereinafter, Winkler et al (2019) , Marié at al. (2020) : the magnetic properties of PM filters and bioaccumulators depend on the concentration and the grain-size of magnetite-like minerals accumulated on the samples, with the magnetic susceptibility being the fastest and most used parameter ( Kapper et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the relationship to COVID-19 mortality in Iran is not unexpected, considering past evidence of association between patterns of PM 2.5 mass concentrations and, for example, cases of cardiovascular mortality: a study of the 2008–2017 period showed that 2009 and 2010 were the most polluted and unhealthy years, the lowest being 2014, coinciding with the minimum and maximum of solar cycle 24, respectively ( Zallaghi et al, 2020 ). Incidentally, note that a small amount of iron oxides arrives as cosmic flux ( Kapper et al, 2020 ). In this regard, the dust concentration in ice cores retrieved from Greenland show a modulation with a period of about 11 years all the way back from at least 100,000 yrs BP, which points to the solar cycle ( Ram et al, 1997 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study of the 2008-2017 period showed that 2009 and 2010 were the most polluted and unhealthy years, the lowest being 2014, coincidentally during the minimum and maximum of solar cycle 24, respectively [29]. Incidentally, note that a small amount of iron oxides arrives as cosmic flux [33]. This relationship has significant practical implications deserving of further research.…”
Section: Discussionmentioning
confidence: 99%